The Effect of Maternal Weight Gain During Pregnancy on Uterine Contraction and Fetal Weight - Zahariah, Sultanah; Rusdiarti, Rusdiarti; Widyana, Erni Dwi (poltekkes kemenkes mataram, 2024)
The duration of labour is influenced by 3 main factors, namely power, passage, passanger. Control of these factors is thought to be able to influence the duration of labor so as to minimize the incidence of complications caused by prolonged labour. Â Maternal nutritional status, one of which is the weight gain during pregnancy, allegedly affects power and passanger as factors that play an important role in labour. This study aims to determine the effect of maternal weight gain during pregnancy on uterine contractions and fetal weight at Srikandi IBI Public Hospital, Jember, East Java. This research is an observational analytic study, a cross-sectional approach with sample size of 92 mothers giving birth at Srikandi General Hospital in Jember. Collected data was analyzed by inferential analysis using path analysis. It was found that the maternal weight gain during pregnancy had a significant effect on the fetal weight (t-value 3.77 with an estimated value of 0.37), but did not affect uterine contractions either in frequency (t-value 1.62) or duration (t -value 0.69). So it can be concluded that the greater maternal weight gain during pregnancy, the greater the fetal weight. Based on the results of this study, it is hoped that health workers will provide assistance so that pregnant women pay attention to increasing body weight during pregnancy based on BMI, so that there are no labor complications due to passanger factors.